1993
DOI: 10.1136/bjo.77.7.413
|View full text |Cite
|
Sign up to set email alerts
|

Congenital glaucoma in the West Bank and Gaza Strip.

Abstract: This study presents the results of all patients with congenital glaucoma who were managed at St John Ophthalmic Hospital, Jerusalem from 1981 to 1990. This involved 118 eyes, 174 surgical procedures, and 460 examinations under anaesthesia. All procedures showed decreasing success rates with time. However, trabeculectomy was clearly the most successful in the hands of general ophthalmologists. Careful, long term follow up with particular regard to both intraocular pressure and detection and treatment of amblyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 14 publications
4
42
1
Order By: Relevance
“…[1][2][3][4][5][6] The success rate of goniotomy and trabeculotomy is related with the age of the patient at the onset of glaucoma and types of abnormalities. 13 When the signs and symptoms of glaucoma were present at birth or over 24 months, the success rate was close to 30%. 6 It has been reported that the surgical results are more favorable if the operation is performed within the first 2 to 12 months of life.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6] The success rate of goniotomy and trabeculotomy is related with the age of the patient at the onset of glaucoma and types of abnormalities. 13 When the signs and symptoms of glaucoma were present at birth or over 24 months, the success rate was close to 30%. 6 It has been reported that the surgical results are more favorable if the operation is performed within the first 2 to 12 months of life.…”
Section: Discussionmentioning
confidence: 98%
“…If known to be variable between ethnic groups, please report) Prevalence of PCG varies between different ethnic groups and ranges from 1 in 18,500 in the UK [14], 1 in 3300 in Andhra Pradesh (Southern India) [15], 1 in 2500 in the middle-east (Saudi Arabia) [16], and 1 in 1250 in the Rom (Gypsy) population of Slovakia [17]. A higher prevalence is observed in ethnic groups in which parental consanguinity is common [18,19].…”
Section: Analytical Validationmentioning
confidence: 99%
“…Combined trabeculotomy-trabeculectomy with time became and remains popular particularly in populations with advanced disease on presentation and those thought to be at greater risk of failure from angle surgery such as in the Middle East and India. [24][25][26][27] However, no prospective comparisons exist to support the argument that combining the procedures improves success.…”
Section: Historymentioning
confidence: 99%